Exosome-driven epigenetic modulation of histone proteins: Pioneering anti-oncogenic and skin health applications - Ekta Yadav; Niket Yadav; Katherine Vanta; Jagjit S Yadav (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2023)
This article explores the use of exosomes in skin care and their potential for modifying epigenetic changes in fibroblasts and other immune regulatory cells of the skin. Exosomes are nanosized extracellular vesicles that play a vital role in intercellular communication by transporting various biomolecules such as proteins, lipids, and nucleic acids between cells. They are released by skin cells and contain various molecules that are essential for skin health, such as growth factors, cytokines, and extracellular matrix proteins. Recent studies have shown that exosomes can modify epigenetic changes in skin cells, particularly histones, and they have the potential to be used as a therapeutic agent in various skin disorders. This article discusses the use of exosomes in skin care and their potential for modulating epigenetic changes in skin cells in response to environmental factors, with a focus on histone modifications.